2019
DOI: 10.1253/circrep.cr-19-0016
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Endarterectomy and Balloon Pulmonary Angioplasty for Chronic Thromboembolic Pulmonary Hypertension ― Similar Effects on Health-Related Quality of Life ―

Abstract: balloon pulmonary angioplasty (BPA) was introduced, which had similarly beneficial effects on hemodynamics, exercise tolerance, and prognosis in patients with inoperable or surgically inaccessible disease. 7-12 In spite of the progress in therapeutic options, some patients who have undergone PEA or BPA still had residual symptoms. 13,14 Health-related quality of life (HRQOL) measurement is a subjective outcome that represents disease impact on a person's function and wellbeing, and can be altered by disease tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…The most affected domains were role physical and physical functioning (Figure 1 ). The RAND‐36 scores from our study are compared with those in three other studies 12 , 17 , 18 in Figure S1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The most affected domains were role physical and physical functioning (Figure 1 ). The RAND‐36 scores from our study are compared with those in three other studies 12 , 17 , 18 in Figure S1 .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported similar patterns of improvement in 6MWD after PEA for CTEPH. 13 , 18 In the UK cohort, the mean 6MWD pre‐PEA was 309 m and increased to 366 m 1‐year post‐PEA. 13 In the Japanese study, the mean 6MWD improved from 281 m preoperatively to 372 m postoperatively, although the improvement was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations